Is Being a TikToker a Sustainable Career? Evidence from a Structural Equation Model on Platform-Dependent Livelihoods and Youth Employment Policy - Phan Nhan Trung (Pancasila International Journal of Applied Social Science, 2026)
This study examines whether content creation on TikTok constitutes a sustainable career pathway for youth or merely a transient income-generating activity that requires supplementary employment. Grounded in Social Cognitive Career Theory, the Theory of Planned Behavior, and the Sustainable Livelihood Framework, the research addresses a critical policy gap in regulating platform-dependent livelihoods within the gig economy. A cross-sectional survey of 420 Vietnamese youth aged 18–30 who generate income through TikTok was analyzed using structural equation modeling (SEM) with maximum likelihood estimation in Stata 19. The model tested six direct effects on Career Sustainability Intention (CSI), mediation through Outcome Expectations (OE), and moderation by Dual-Career Orientation (DUA). Platform Dependency Risk (PLT) emerged as the strongest predictor of career sustainability intention (β = −0.345, p < .001), followed by Self-Efficacy in Content Creation (SE, β = 0.237, p = .001), Skill Diversification (SKD, β = 0.224, p < .001), and Perceived Income Stability (INC, β = 0.216, p < .001). Bootstrap mediation analysis confirmed the SE → OE → CSI pathway as significant (p = .047). The moderation hypothesis for Dual-Career Orientation was rejected (p = .632). Only 8.1% of respondents were classified as having a sustainable career, while 22.1% were categorized as high risk. The findings provide empirical justification for government intervention in platform-dependent labor markets, including digital skills certification frameworks, platform labor regulation, social protection mechanisms for content creators, and youth career guidance policies that incorporate the realities of the creator economy. This is among the first studies to apply a full SEM framework with mediation and moderation to assess TikTok content creation as a career choice in a developing-economy context, offering evidence-based policy recommendations to regulate an emerging, largely unregulated labor sector.